The Influence Of Service Quality, Digital Marketing, Price, Lifestyle, And Purchasing Power On Consumer Purchasing Decisions In WW Collection Pungging - Maylindah Angelina Akbar; Yuliasnita Verlandes; Imam Baidowi (International Journal of Management Research and Economics, 2025)
This study aims to examine and analyze the effect of service quality, digital marketing, price, lifestyle and purchasing power on purchasing decisions of WW Collection consumers. This research uses a quantitative descriptive approach. The technique collected is in the form of primary data by means of a questionnaire which is distributed to respondents called a questionnaire. The data collection technique uses the Purposive Sampling technique, which is a sample purchasing technique with certain considerations, namely using certain criteria, such as WW Collection consumers who have shopped at least once either through social media or come directly to the store, with a total of 265 respondents at the WW Collection store. The results showed that the variables of service quality, digital marketing and price had a partially significant effect on purchasing decisions at the WW Collection Pugging store. However, the lifestyle and purchasing power variables do not significantly influence purchasing decisions at the WW Collection Pugging store. In the variables of service quality, digital marketing, price, lifestyle, and purchasing power, they influence purchasing decisions simultaneously at the WW Collection Pugging store. As a form of the implications of this research, it is hoped that the influential variables can be evaluated and maintained even better by the WW Collection.